2016
DOI: 10.3389/fnhum.2016.00591
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Signatures in the Brain: Semantic Pre-Activation during Language Comprehension

Abstract: There is broad agreement that context-based predictions facilitate lexical-semantic processing. A robust index of semantic prediction during language comprehension is an evoked response, known as the N400, whose amplitude is modulated as a function of semantic context. However, the underlying neural mechanisms that utilize relations of the prior context and the embedded word within it are largely unknown. We measured magnetoencephalography (MEG) data while participants were listening to simple German sentences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
66
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 90 publications
19
66
3
Order By: Relevance
“…We therefore argued that this preactivation should modulate the N400 component—the ERP component typically associated with the activation of semantic information (see Kutas & Federmeier, , for a review). The distribution (though more widely distributed; see Figure ) and the time course of the waveform that was modulated by adverb impact strongly suggest that this is indeed an N400 modulation (see Maess, Mamashli, Obleser, Helle, & Friederici, , for a recent comparable magnetoencephalography finding).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…We therefore argued that this preactivation should modulate the N400 component—the ERP component typically associated with the activation of semantic information (see Kutas & Federmeier, , for a review). The distribution (though more widely distributed; see Figure ) and the time course of the waveform that was modulated by adverb impact strongly suggest that this is indeed an N400 modulation (see Maess, Mamashli, Obleser, Helle, & Friederici, , for a recent comparable magnetoencephalography finding).…”
Section: Discussionmentioning
confidence: 87%
“…When readers in the present experiment arrived at the adverb, the event conveyed by the sentence was already largely expressed, and this circumstance might have contributed to the observed pattern. And even though results from Maess et al (2016) demonstrate that a minimal context suffices to elicit N400 effects between verbs that are more as compared to less informative about future input 7. Mean (cloze value * frequency * ONS)ˆ2 1 (1 1 (cloze value * frequency * ONS)ˆ2 j participant) 1 (1 j item).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a recent MEG-study found effects of semantic predictability at the main verb of the 114 sentence (Maess et al, 2016). Specifically, a reversed N400m effect, the magnetic 115 pendant of the N400, was reported for the verb, with highly predictive verbs eliciting a 116 stronger N400m relative to verbs with a lower predictability.…”
mentioning
confidence: 95%
“…To 157 capture a potential behavioral impact of the TMS induced perturbation that is usually 158 quantified in terms of decreased response accuracy or increased response speed 159 (Hartwigsen, 2015), a lexical decision task was included. Motivated by a previous 160 study that used similar sentences and found effects already at the mid-sentence verb 161 position in addition to the sentence-final noun position (Maess et al, 2016), the 162 present study applied TMS over pIFG and pSTG/STS at verb onset. This allowed for 163 testing whether the perturbation effect would only impact processing during the 164 stimulated period (i.e., processing of the verb) or outlast verb presentation and also 165 impact integration of the final noun into a sentence.…”
mentioning
confidence: 99%